Translacteal infection of baby calves, feeder pigs and puppies during lactation - GEORGOULAKIS (Α.Ε. ΓΕΩΡΓΟΥΛΑΚΗΣ), A. E.; PAPAZACHARIADOU (Μ. ΠΑΠΑΖΑΧΑΡΙΑΔΟΥ), M.; GOLOMAZOU (E. ΓΚΟΛΟΜΑΖΟΥ), E.; THEODORIDIS (Ι. ΘΕΟΔΩΡΙΔΗΣ), Y. (Journal of the Hellenic Veterinary Medical Society, 2017)
The present study examines the probability of translacteal transmission via colostrum of gastrointestinal nematode infections in baby calves, feeder pigs and puppies. Colostrum samples from dairy cows, sows and bitches were examined for the presence of larvae. The results of the study are as follows: The colostrum of 12 cows out of 342 examined was infected (3,5%) and the larvae identified were Toxocara, vitulorum, Strongyloides sp. And Bunostomum sp. The colostrum of 2 sows out of 125 examined was infected with larvae of Strongyloides sp. (1,6%). The colostrum of 123 bitches out of 217 examined (56,7%) was shown to be positive for Toxocara canis, Ancylostoma sp. and Strongyloides sp.